Literaga 2.0 : Literasi Kesehatan melalui Permainan Ular Tangga di SDN Jatinangor Kabupaten Sumedang - Retasari Dewi; Susanne Dida; Elnovani Lusiana (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The high incidence of outbreaks of snack poisoning among elementary school students in 2024 reflects the impact of systemic problems in Indonesia’s educational environment. Increasing students’ knowledge at school is one of the important steps to empower them to choose safe and healthy snacks for consumption. The health literacy activity through snakes and ladders game at SDN Jatinangor aims to improve students’ health literacy regarding the importance of choosing safe and healthy snacks. This game is a refinement of Literaga 1.0 which was previously tested and successfully increased students’ knowledge of a clean and healthy lifestyle in 2023. The activity involved 35 Padjadjaran University students as facilitators and 89 Jatinangor Elementary School students. The method used was game-based learning, which integrates learning about healthy eating patterns in a game format. Evaluation results using pre-test and post-test showed a significant increase in student knowledge (t Stat = -22.38, P-value <0.05). These results indicate that the Literaga 2.0 educational game board is effective in increasing students’ knowledge about safe and healthy snacks. In the future, further support from schools and families is needed to provide safe and healthy food/snack alternatives for school students.